TAKLIK TALAK SEBAGAI UPAYA PERLINDUNGAN TERHADAP HAK ISTRI - Saberiani HM (IAIN BONE, 2021)
AbstractThis study aims to determine the urgency of taklik talak in marriage and the effectiveness of reciting şīgat taklik talak as an effort to protect the rights of wives in Barebbo district, Bone regency. The results showed that taklik talak in marriage is one of the preventive measures so that the wife's rights can be guaranteed and avoid the possibility of abuse by the husband. Taklik talak in Barebbo Subdistrict is understood as a means of education for the husband in realizing his responsibilities, almost all of which have been described in şīgat taklik talak. The majority of the community stated that taklik talak as an effort to protect the rights of wives in Barebbo district is still effective. This is reinforced by the condition of the household of a husband and wife who pledge taklik talak, looks harmonious, meaning that the wife's rights are guaranteed during the marriage. The low divorce rate that occurs in Barebbo subdistrict due to the husband's negligence in providing a living is also an indication that the taklik-talak function which binds the husband's responsibility towards his wife is quite effective.Keywords: Şīgat; Taklik Talak; Wife’s RightsPenelitian ini bertujuan untuk mengetahui urgensi taklik talak dalam perkawinan serta efektivitas pembacaan şīgat taklik talak sebagai upaya perlindungan terhadap hak-hak istri di Kecamatan Barebbo Kabupaten Bone. Hasil penelitian menunjukkan bahwa taklik talak dalam perkawinan adalah sebagai salah satu usaha preventif agar hak istri dapat terjamin dan terhindar dari kemungkinan perlakuan semena-mena suami. Taklik talak di Kecamatan Barebbo dipahami sebagai sarana edukasi bagi suami dalam menyadari tanggung jawabnya yang hampir semuanya sudah dijabarkan pada şīgat taklik talak. Mayoritas masyarakat menyatakan bahwa taklik talak sebagai upaya untuk melindungi hak-hak istri di Kecamatan Barebbo masih efektif. Hal ini diperkuat dengan keadaan rumah tangga pasangan suami istri yang mengikrarkan taklik talak terlihat harmonis, artinya hak istri terjamin selama berumah tangga. Rendahnya angka perceraian yang terjadi di Kecamatan Barebbo yang disebabkan oleh kelalaian suami dalam hal pemberian nafkah juga menjadi indikasi bahwa fungsi taklik talak yang mengikat pertanggungjawaban suami terhadap istrinya cukup efektif.Kata Kunci: Şīgat; Taklik Talak; Hak Istri.